Mass Media in Social and Political Participation - Piriyasanti, Sirisak; Phuengpha , Noppawan (Procedia of Social Sciences and Humanities, 2024)
Online media significantly enhances public political participation by providing accurate, comprehensive, and diverse information. It helps the public understand current situations, analyze government policies, and critique them rationally. Mass media, including television, radio, newspapers, and digital platforms, has transformed society's engagement in social and political processes. It plays a crucial role in social and political participation by providing information, promoting social activities, and inspiring collective action. However, the influence of mass media on social and political behavior is complex and can lead to misinformation, political bias, and polarization. The objectives is; to examine the role of mass media in influencing public participation and to analyze the application of the concept of political participation in understanding the relationship between mass media and public political engagement. This article using a quantitative approach. Mass media, from traditional newspapers to digital platforms, has significantly influenced social and political participation. Despite challenges like misinformation and superficial online participation, it remains a powerful force in shaping citizen engagement.